2021
DOI: 10.3390/cancers13040825
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Metabolic Conditions Impacts the Regulation of IGF-II/H19 Imprinting Status in Prostate Cancer

Abstract: Prostate cancer is the second major cause of male cancer deaths. Obesity, type 2 diabetes, and cancer risk are linked. Insulin-like growth factor II (IGF-II) is involved in numerous cellular events, including proliferation and survival. The IGF-II gene shares its locus with the lncRNA, H19. IGF-II/H19 was the first gene to be identified as being “imprinted”—where the paternal copy is not transcribed—a silencing phenomenon lost in many cancer types. We disrupted imprinting behaviour in vitro by altering metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…José Manuel Cózar-Olmo et al con rmed that functional type 2 diabetes (T2DM) related mutations might affect the risk of prostate cancer from the genetic level [36]. Georgina Kingshott et al also found that diabetes could directly affect the regulatory growth factors related to cancer, and changing living habits might signi cantly reduce the risk of prostate cancer and other cancers [37]. For the problem of recurrence after prostatectomy, relevant research showed that patients with diabetes had a higher risk of recurrence [38].…”
Section: Discussionmentioning
confidence: 99%
“…José Manuel Cózar-Olmo et al con rmed that functional type 2 diabetes (T2DM) related mutations might affect the risk of prostate cancer from the genetic level [36]. Georgina Kingshott et al also found that diabetes could directly affect the regulatory growth factors related to cancer, and changing living habits might signi cantly reduce the risk of prostate cancer and other cancers [37]. For the problem of recurrence after prostatectomy, relevant research showed that patients with diabetes had a higher risk of recurrence [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are not many data in PC, there are reports about the role of IGF2 -mRNA and its peptide in PC, with a decrease of 80% in PC compared to non-neoplastic adjacent prostate ( Kingshott et al, 2021 ). There are also data, including the over-expression patterns of IMP3 (messenger RNA binding protein 3 related to IGF2 ) in PC, related to patients’ poor prognosis ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 4 most significant hits from the RNA sequencing analysis were subjected to validation using real-time quantitative PCR as described previously ( 24 ). qPCR was performed using SYBR Green (Applied Biosystems) on a StepOne RealTime PCR machine (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%